Middleton, Colonial America: A History, 1607-1760 - Bailey, Raymond (Teaching History: A Journal of Methods, 1995)
Middleton's book is intended to serve as the primary text for courses on early American history, and teachers will find that it merits serious consideration. The first seven chapters, comprising almost 200 pages, provide a relatively straightforward and heavily chronological description of seventeenth-century developments. Nine chapters then follow with a largely topical discussion of eighteenth-century political, social, and economic life.